Confounding Due to Pre-Existing Diseases in Epidemiologic Studies on Sedentary Behavior and All-Cause Mortality: A Meta-Epidemiologic Study - De Moraes-Ferrari, G (Elsevier Inc., 2020)
Purpose: We examined the influence of confounding due to pre-existing diseases in prospective studies on sedentary behavior and all-cause mortality. Methods: We analyzed 25 studies included in systematic reviews. The risk of confounding due to pre-existing diseases was assessed by five methodologic characteristics. Results: Sedentary behavior was associated with higher all-cause mortality. Studies with short average follow-up length had stronger magnitudes of association: 1 to less than 5 years (hazard ratio [HR], 1.58; 95% confidence interval [CI], 1.28–1.94), 5 to 9 years (HR, 1.24; 95% CI, 1.16–1.31), and 10 years or more of follow-up (HR, 1.20; 95% CI, 1.10–1.31). Studies that did not adjust for diseases at baseline, did not exclude deaths in the first years of follow-up, and did not exclude participants with diseases/conditions showed stronger associations. Studies with higher risk of confounding because of pre-existing diseases (HR, 1.40; 95% CI, 1.27–1.54) showed stronger association than lower risk studies (HR, 1.18; 95% CI, 1.10–1.27). Studies excluding participants with diseases at baseline had weaker associations compared with studies adjusting for diseases in models. Conclusions: Sedentary behavior was associated with increased all-cause mortality, although confounding due to pre-existing diseases may bias the magnitude of the association. © 2020 Elsevier Inc.
Keywords: Epidemiologic studies; Mortality; Sedentary behavior; Confounding; Bias